2021
DOI: 10.1139/cjps-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphological responses of gerbera seedlings to narrow-band lights with different light spectral combinations as sole-source lighting in a controlled environment

Abstract: To optimize light-emitting diode (LED) spectral recipes for gerbera (Gerbera jamesonii) seedling propagation, seed germination and seedling morphology, biomass, flowering, and storage quality were observed in four cultivars, ‘Midi Dark Purple’, ‘Majorette Red Dark Eye’, ‘Maxi Pink’, and ‘Maxi White’, under six spectrum treatments: (1) FL, cool white fluorescent light; (2) RB, a photon flux ratio of 85% red and 15% blue (RB-LED); (3) RB + UVB, RB-LED combined with 0.5 μmol·m−2·s−1 of ultraviolet-B; (4) RB + UVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Differently, the addition of FR at ≥20 µmol m −2 s −1 to RB-LED accelerated the flowering of at least some long-day plants such as snapdragons, but did not affect the flowering of day-neutral or short-day plants [61]. However, in our recent study on gerbera transplants under sole-source lighting, when adding low-level UVB, UVA, green, or far-red light to RB-LED (15% B) and keeping the same total PPFD for all treatments, the flowering time after transplanting was not different among the different lighting treatments [63]. When the low levels of other light wavelengths were added to RB-LED, and the phytochrome activity was changed little (with the PPS values varying 0.84−0.88).…”
Section: Plant Genotype Lighting Treatments Effects Of Lighting Treat...mentioning
confidence: 58%
“…Differently, the addition of FR at ≥20 µmol m −2 s −1 to RB-LED accelerated the flowering of at least some long-day plants such as snapdragons, but did not affect the flowering of day-neutral or short-day plants [61]. However, in our recent study on gerbera transplants under sole-source lighting, when adding low-level UVB, UVA, green, or far-red light to RB-LED (15% B) and keeping the same total PPFD for all treatments, the flowering time after transplanting was not different among the different lighting treatments [63]. When the low levels of other light wavelengths were added to RB-LED, and the phytochrome activity was changed little (with the PPS values varying 0.84−0.88).…”
Section: Plant Genotype Lighting Treatments Effects Of Lighting Treat...mentioning
confidence: 58%
“…Sole-source lighting with RB-LEDs is commonly used for indoor transplant production. A recent study in our lab indicated that RB-LEDs (15%B) can potentially replace fluorescent light, but the trichromatic lights appear to be unnecessary for the indoor production of compact gerbera transplants [ 137 ]. Compared with red or blue LEDs alone, RB-LEDs (50%B) caused more compact seedlings in bedding plants such as impatiens, petunias, and salvia [ 57 ].…”
Section: Application Of Blue Leds In Mediating Plant Elongation For C...mentioning
confidence: 99%